Konsep Psikologi Transpersonal Dalam Mengenal Sebuah Makna Bahagia Dalam Islam - Naan Naan; Naufal Nurfajri (HUMANISTIKA : Jurnal Keislaman, 2022)
This study aims to analyze a concept of Transpersonal Psychology in recognizing a meaning of happiness in Islam from the views of Muslim scholars assessing aspects of the meaning of happiness that occurred in the 21st century which previously had failed to use a (western) understanding approach that sidelined the area of one's spirituality from the aspect of individual happiness. And there is also this study whose writing relies on collecting data from figures known as interpretative methods and exploring sources that are considered relevant to this discussion. The rotation of the focus of this discussion answers the problem of each individual's happiness in part from the happiness of the world and also the happiness of the hereafter by using a Sufistic spiritual approach, combining the two to get absolute happiness or eternal happiness that is not temporary.